Effects of sorghum genotype and processing method on production characteristics and growth performance of nursery pigs - Froeschner, J.R.; Cheng, Z.J.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three sorghum varieties that varied in starch composition were fed to Phase II and Phase III pigs to determine if feeding sorghum high in waxiness provided a benefit. In addition, each variety was fed as a meal, standard pellet, and an expanded pellet. As level of waxiness increased, pellet durability index increased numerically and the amount of fines produced decreased numerically. In addition, thermal processing of the diets increased the feeding value. Sorghum genotype had little effect on pig performance.
Keywords: Swine; Sorghum; Waxy sorghum; Expanded pellet; Nursery pigs